Super-Saturated SNEDDS with Vegetable Oils: Formulation and Evaluation - Mittal, Heena; Kaushik, Sudhakar; Bhatt, Bhawana; Babbar, Assem (International Journal of Pharmaceutical Investigation, 2025)
Background Solubility is the most vital parameter in the formulation of different drug delivery systems and one of the core concepts of the formulations. More than 50% of the new drug molecules are facing poor solubility issues. Poor solubility leads to limited bioavailability. Dabigatran Etexilate (DBE) is an anti-coagulant drug belonging to BCS class II drug having low solubility and high permeability and its oral bioavailability is 30%. Self-Nano-Emulsifying Drug Delivery System (SNEDDS) is used for the enhancement of solubility and bioavailability of the drug. However, SNEDDS has some major disadvantages such as less drug loading and precipitation of the drug in the GI. Therefore, a Supersaturated Self Nano Emulsifying Drug Delivery System (S-SNEDDS) is prepared. Materials and Methods A ternary phase diagram was constructed to determine the nano-emulsion region. Liquid S-SNEDDS was prepared by mixing castor oil, Transcutol HP and Cremophor EL with DBE including Sodium taurocholate as a precipitate inhibitor The Liquid S-SNEEDS was further converted to Solid S-SNEDDS by using Aerosil 200 as an adsorbent to form a more stable dosage form. A higher amount of Aerosil 200 was used which exhibits good flow properties and preserved the self-emulsifying properties of Liquid SNEDDS. Results and Conclusion The final formulation was characterized using DSC and SEM and evaluated for in vitro dissolution. All the evaluations demonstrated that S-SNEDDS had particle size less than 200 nm, PDI was less than 0.5 and zeta potential was between -25 and -45. In vitro dissolution demonstrated that higher drug release was found in capsules incorporated with S-SNEDDS as compared to SNEDDS capsules.
Keywords: Dabigatran Etexilate; Nano-Emulsion; Solubility; Super-Saturated Self Nano-Emulsifying Drug Delivery System